2000
DOI: 10.1016/s1074-7613(00)00045-5
|View full text |Cite
|
Sign up to set email alerts
|

CD40 Triggering of Heterodimeric IL-12 p70 Production by Dendritic Cells In Vivo Requires a Microbial Priming Signal

Abstract: CD40 ligation triggers IL-12 production by dendritic cells (DC) in vitro. Here, we demonstrate that CD40 cross-linking alone is not sufficient to induce IL-12 production by DC in vivo. Indeed, resting DC make neither the IL-12 p35 nor IL-12 p40 subunits and express only low levels of CD40. Nevertheless, after DC activation by microbial stimuli that primarily upregulate IL-12 p40 and augment CD40 expression, CD40 ligation induces a significant increase in IL-12 p35 and IL-12 p70 heterodimer production. Similarl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

50
412
2
4

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 516 publications
(473 citation statements)
references
References 42 publications
50
412
2
4
Order By: Relevance
“…2B). Since IL-12p70 production requires at least two activating signals for DC [16,24,25], we included LPS in the co-cultures to provide the additional stimulus. We found that this had an additive effect on the levels of IL-12p40 produced, but IL-12p70 levels remained barely detectable (<20 pg/mL) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2B). Since IL-12p70 production requires at least two activating signals for DC [16,24,25], we included LPS in the co-cultures to provide the additional stimulus. We found that this had an additive effect on the levels of IL-12p40 produced, but IL-12p70 levels remained barely detectable (<20 pg/mL) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…CD40-CD40L interaction is essential for CD8 T cellmediated IL-12p70 production CD40 stimulation is important for IL-12p70 production by DC [25,29,30]. To investigate whether CD40-CD40L interactions were involved in our system, we obtained DC from CD40 -/-mice for coculture with activated CD8 T cells and LPS (Fig.…”
Section: Cd8 T Cell-mediated Il-12p70 Production Is Contact-dependentmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Thus, IL-12 is secreted as an early pro-inflammatory cytokine in response to infections. 3 Additional amplifying signals such as interferon-g (IFN-g), 4 IL-15 5 or cluster of differentiation (CD)40L-CD40 cell-cell interactions 6 are necessary for the optimal production of biologically active IL-12. Conversely, IL-12 is negatively regulated through cytokines such as IL-10 and transforming growth factor-b1 (TGF-b1).…”
Section: Open Questionsmentioning
confidence: 99%
“…In addition, molecules derived from bacterial or viral products, as well as pro-inflammatory cytokines (TNFα and IFNγ) and T cell signals such as CD40-ligand (CD40L), can promote the secretion of IL-12p70 and TNFα from DC thereby promoting a Th1-skewed response (Schulz et al, 2000;Vieira et al, 2000). In contrast, anti-inflammatory molecules such as IL-10, prostaglandin E2 (PGE2) and corticosteroids can inhibit RTDC maturation and cytokine production and therefore promote a Th2-skewed response (Kalinski et al, 1997;Faries et al, 2001;Kalinski et al, 2001).…”
Section: Peripheral T Cell Regulationmentioning
confidence: 99%